Processing and characterization of tissue adhesive from rice starch nanocomposites - Watee Puntuwat (2018)
The objective of this work is make tissue adhesives agent from Thai rice starch, then test the final products for scientific and medical properties following the laws of Thai health ministry, to demonstrate that this product can be used safely, as same as the standard product. The principal raw material is pharmaceutical grade, Thai rice starch powder. The additives are hydroxyapatite (HA) nanopowder, carboxymethylcellulose, lactic acid, gelatin, polyvinylalcohol and glycerol. All materials will be mixed in distilled water under high temperature, and dried into starch tissue adhesives plate hydrogel. The final product will be kept in medical package and sent for sterilization by gamma radiation. These products will be characterized by scanning electron microscopy (SEM), x-ray diffraction (XRD), stability in water, and adhesive bond strength test in wet environment. © (2010) Trans Tech Publications.